Effects of the MIND diet and physical activity on cognitive domains in the elderly. (31st December 2021) - Holland, Thomas Monroe; Agarwal, Puja; Dhana, Klodian; Halloway, Shannon; Desai, Pankaja; Wang, Yamin; Aggarwal, Neelum T; Barnes, Lisa L; Rajan, Kumar B
Abstract: Background: Diet and physical activity (PA) are important for cognitive health, but few studies have examined whether there is a synergistic relationship with cognitive decline in older adults. In this study, we investigated whether the combination of a high MIND diet score and high, device‐measured, PA has a stronger relationship with global cognitive decline and specific cognitive domains when compared to other combinations of MIND diet score and PA levels, Method: We examined the association of MIND diet and PA interactions on global cognition and five cognitive domains in 264 participants without cognitive impairment from the Rush Memory and Aging Project. Diet was assessed using a validated 144‐item food frequency questionnaire with objective physical activity measured by Actical. Cognition was assessed using a 19‐test cognitive battery from which a global composite score and 5 domains were derived. Participants (mean age = 79± SD 7.7 years; 75% female) were followed for an average of 6.3 ± SD 2.7 years and separated into 9 categorical combinations of MIND diet score and PA (high, moderate, low for MIND diet x high, moderate, low for PA), with low MIND diet and low PA serving as the reference. Linear mixed models adjusted for age sex, education, ApoE‐4, late life cognitive activity, self‐reported physical activity, smoking, and caloric intake. Result: Adherence to a high MIND/high PA regimen over time versus low MIND/low PA was associated with a 62.5% slower rate of decline in global cognition (β=0.12, p=0.0001). We also found similar associations for episodic memory (β=0.13, p=0.0006), semantic memory (β=0.1, p=0.005), perceptual speed (β=0.05, p=0.03), and working memory (β=0.08, p=0.006) but not visuospatial ability (β=0.05, p=0.15.). Further, it was determined that the high MIND/high PA combination improved a broader range of cognitive domains over time, than either the high MIND/low PA, or low MIND/high PA, versus low MIND/low PA. (Figure 1) Conclusion: Adherence to a high MIND diet/high PA regimen has a greater impact on cognitive decline and specific cognitive domains versus alternate combinations of MIND diet and Physical Activity.